Fiscal Federalism and Economic Performance - New Evidence from Switzerland - Heiko T. Burret; Lars P. Feld; Christoph A. Schaltegger (Center for Economic Studies and ifo Institute (CESifo), 2018)
The link between federalism and economic performance is still ambiguous. Aiming at clarification, we improve on a widespread shortcoming by measuring federalism not just by one variable but by various institutions that constitute it. To this end, Switzerland provides for a laboratory as its 26 cantons share a common framework, while the extent of federalism varies between the cantons and across time. By exploiting this setting, the paper provides evidence for the expected heterogeneity: The impact of federalism on economic performance differs conditional on the federal instrument considered. Overall, instruments of competitive federalism appear to improve economic performance of the cantons, while adverse effects are reported for cooperative elements.
Keywords: H77; H73; O43; O47; 330; fiscal federalism; economic growth; fiscal competition; fiscal equalization